2007
DOI: 10.1016/s0828-282x(07)70886-3
|View full text |Cite
|
Sign up to set email alerts
|

Arterialization of a vein graft promotes cell cycle progression through Akt and p38 mitogen-activated protein kinase pathways: Impact of the preparation procedure

Abstract: It was concluded that two-week arterial implantation stimulates proliferation signalling and promotes the cell cycle in vein grafts. Replacement of the conventional preparation procedures with pharmacological vasorelaxation restricts the activation of proliferation and cell cycle progression, and can be beneficial for improving vein graft patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Topical MAPK inhibitors significantly suppressed graft disease in a rabbit inter-positional model of vein grafting [78] , although not cell-specific, this provides further evidence for the role of MAPK in vein graft failure. Moreover, pharmacological vasorelaxation suppressed p38 activity and restricted the activation of proliferation and cell cycle progression in the porcine carotid jugular interposition graft [79] . Further evidence for the inhibition of inflammatory processes in vein graft disease is scarce.…”
Section: Intimal Hyperplasia and The Endotheliummentioning
confidence: 94%
“…Topical MAPK inhibitors significantly suppressed graft disease in a rabbit inter-positional model of vein grafting [78] , although not cell-specific, this provides further evidence for the role of MAPK in vein graft failure. Moreover, pharmacological vasorelaxation suppressed p38 activity and restricted the activation of proliferation and cell cycle progression in the porcine carotid jugular interposition graft [79] . Further evidence for the inhibition of inflammatory processes in vein graft disease is scarce.…”
Section: Intimal Hyperplasia and The Endotheliummentioning
confidence: 94%
“…61 In the porcine carotid jugular interposition graft, it has been suggested that the use of pharmacological vasorelaxation (PV) suppresses p38 activity and restricts the activation of proliferation and cell cycle progression. 62 NF-κB regulates the leukocyte adhesion cascade (e.g. VCAM-1) and can contribute to sub-endothelial transmigration and the release of pro-inflammatory mediators.…”
Section: Glucocorticoids and Vein Graft Disease (Intimal Hyperplasia)mentioning
confidence: 99%